Pendekatan Supervisi Kepala Sekolah yang Efektif dalam Meningkatkan Profesionalisme Guru: Systematic Literature Review - Mirna Rasuani; Fitri Aprilianty; Isna Susmita (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine the effective supervision approaches of school principals in improving teacher professionalism through a Systematic Literature Review (SLR) method. Teacher professionalism is a crucial factor in improving the quality of education, where the principal acts as an academic supervisor. A total of 15 relevant scientific articles from 2020 to 2025 were systematically analyzed to identify supervision strategies, implementation challenges, and their impact on teacher quality. The study results indicate that approaches such as clinical, collegial, Total Quality Management (TQM)-based supervision, as well as democratic and participatory approaches are effective in improving teachers' pedagogical, professional, social, and personal competencies. However, several obstacles were also identified, such as minimal follow-up, the dominance of administrative approaches, and a lack of innovation in supervision implementation. The novelty of this study lies in the synthesis of supervision models that are contextual and relevant to the challenges of education in the digital era. This study provides theoretical and practical contributions by offering recommendations for applicable, sustainable, and collaborative supervision strategies to support teacher professional development in various educational units.